The balance of payments statistics of the United States: a review and appraisal - United States ([Washington: U.S. Govt. Print. Off.], 1965)
This review contains statistical analysis on some of the working findings of the United State committee on balance of payment for the period1963.
asm; 05/03/19
Loans
Keywords: Balance of payments; Commercial statistics